The Utilization of Rice Husk Charcoal as a Source of Silica in The Synthesis of Forsterite in Air Medium - Haryono MT; Solihudin Solihudin (Balai Besar Keramik, 2020)
Forsterite has a heat resistance property at high temperatures so it has the potential as a refractory material. As the main agricultural commodity in Indonesia, rice is a potential raw material as a source of amorphous silica and carbon through the partial burning process of rice husks. This study aims to determine the effect of calcination temperature in air medium on the process of forming forsterite from MgCO3 and rice husk charcoal. The forsterite/carbon synthesis was carried out at a mole ratio of MgCO3 to SiO2 of 2:1. The research method includes the preparation of rice husk charcoal by gasification; synthesis of forsterite with variations in calcination temperature at 700, 800, 900, and 1000 oC for 2 hours; and characterization of synthesis results using FTIR and XRD. The results showed that the higher the calcination temperature, based on the formation of bonds from the results of FTIR analysis and XRD diffractogram, the more the forsterite structure was formed. Calcination at 1000 oC is the optimum temperature for the formation of forsterite.